The Biosynthesis, Accumulation, and Antimicrobial Potential of Phytoalexin and Natural Product in Plant and Animal Defense System - Mamman, Muazu; H. A. Muhammed; I. I. Akowe; S. Abdulhakeem; J. Iyaji (RADINKA JAYA UTAMA PUBLISHER, 2024)
ABSTRACT Most plant potential to resist pathogenic infections requires some sophisticated defense system which basically involves the production of low-molecular-weight antimicrobial metabolites known as phytoalexins. These compounds are known to exhibit toxicity towards a wide spectrum of pathogens, such as ffungi, bacteria, nematodes, and other organisms. This review delves into the diverse chemical structures and biosynthetic pathways of phytoalexins across various plant familie and some higher animals human alike. We examine the mechanisms of phytoalexin accumulation, through de novo synthesis, enzymatic biocatalysis activities, and the influence of biotic and abiotic elicitors. Understanding the complex connection between phytoalexin biosynthesis, accumulation, and antimicrobial activity is crucial for developing effective disease management strategies. By employing modern molecular biology tools, researchers can elucidate the genetic pattern of phytoalexin production and identify key genes involved in resistance and susceptibility. Keywords: Phytoalexins, biosynthesis, accumulation, antimicrobial, plant defense, elicitors, metabolites.